Analyzing Figurative Language as a Reflection of Social and Emotional Loneliness in Sara Teasdale’s Selected Works - Firdaus, Gayatri Yuridani; Adeline Grace M. Litaay (CV. Era Digital Nusantara, 2025)
Loneliness, characterized by feelings of emptiness, isolation, and longing, is a complex emotional experience with significant psychological and social implications. This research discusses the sense of loneliness in Sara Teasdale’s poems: “Alone”, “Ebb Tide”, “Sleepless”, “The Treasure”, “Compensation”, and “Deep in the Night”. The aims of this research are to explain types of figurative languages used in the six poems of Sara Teasdale, and to describe types of loneliness in those poems. This study addresses this gap by focusing exclusively on loneliness as the central theme and applying a dual-lens analysis of figurative language and loneliness theory to Sara Teasdale’s poetry. This resarch applies intrinsic and extrinsic approaches. It employs a descriptive qualitative method. The source of data in this research is the six poems of Sara Teasdale: “Alone”, “Ebb Tide”, “Sleepless”, “The Treasure”, “Compensation”, and “Deep in the Night”. It is found in the result of the analysis that there are 6 types of figurative languages in 6 poems, those are: metaphor, simile, personification, hyperbole, metonymy, paradox, symbolism, and anaphora. These devices not only enrich the aesthetic quality of the poems but also intensify the emotional portrayal of loneliness. It is also found that Sara Teasdale suffers from both social and emotional loneliness which is revealed through the figurative language analysis and theory of loneliness from Robert S. Weiss. This research contributes to literary studies by linking the use of figurative language with psychological theories of loneliness, exploring human experiences that are often difficult to articulate directly.